A genome-wide scan for quantitative trait loci linked to obesity phenotypes among West Africans - Chen, G.; Adeyemo, A.A.; Johnson, T.; Zhou, J.; Amoah, A.; Owusu, S.; Acheampong, J.; Agyenim-Boateng, K.; Eghan Jr., B.A.; Oli, J.; Okafor, G.; Abbiyesuku, F.; et al. (International Journal of Obesity, 2005)
OBJECTIVE: To identify quantitative trait loci (QTL) for three obesity phenotypes: body mass index (BMI), fat mass (FM) and percent body fat (PBF) in West Africans with type 2 diabetes (T2DM). DESIGN: An affected sibling pair (ASP) design, in which both siblings had T2DM. Obesity was analyzed as a quantitative trait using a variance components approach. SUBJECTS: Sib-pairs affected with T2DM from the Africa America Diabetes Mellitus (AADM) study, comprising 321 sibling pairs and 36 half-sibling pairs. MEASUREMENTS: Weight was measured on an electronic scale to the nearest 0.1 kg, and height was measured with a stadiometer to the nearest 0.1 cm. Body composition was estimated using bioelectric impedance analysis (BIA). Genotyping was carried out at the Center for Inherited Disease Research (CIDR) with a panel of 390 trinucleotide and tetranucleotide repeats. RESULTS: The obesity-related phenotype showing the strongest linkage evidence was PBF on chromosome 2 (LOD 3.30 at 72.6 cM, marker D2S739). Suggestive linkage to FM was found on chromosomes 2 (LOD 2.56 at 80.4 cM) and 5 (LOD 2.25 at 98 cM, marker D5S1725). The highest LOD score for BMI was 1.68 (chromosome 4, 113.8 cM). The areas of linkage for the three phenotypes showed some clustering as all three phenotypes were linked to the same regions of 2p13 and 5q14, and our study replicated linkage evidence for several regions previously reported in other studies. CONCLUSION: We obtained evidence for several QTLs on chromosome 2, 4 and 5 to three obesity phenotypes. This study provides data on the genetics of obesity in populations that are currently under represented in the global effort directed at understanding the pathophysiology of excess adiposity in free living individuals.
Keywords: Genetics; Genome scan; Type 2 diabetes; West Africa